2020
DOI: 10.3390/ani10101925
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Acute-Phase Protein Response Associated with the Different Pathological Forms of Bovine Paratuberculosis

Abstract: In this study, the concentrations of two acute-phase proteins (APPs), haptoglobin (Hp) and serum amyloid A (SAA), were quantitatively assessed in serum samples from cattle naturally infected with paratuberculosis (PTB). APP profiles were compared across 190 animals classified according to the different pathological forms associated with infection: uninfected (n = 59), with focal lesions (n = 73), multifocal lesions (n = 19), and diffuse paucibacillary (n = 11) and diffuse multibacillary lesions (n = 28). Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
0
11
0
1
Order By: Relevance
“…The differential proteomic analysis combined with immunohistochemical validation highlighted several changes occurring in PTB tissues and provided novel molecular information on the distinct levels of tissue involvement that can be found within the asymptomatic, paucibacillary condition. Other studies have investigated the levels of inflammatory acute-phase proteins (haptoglobin and serum amyloid A) developed during the course of MAP infection in serum as potential serum markers for the identification of sub-clinically infected cows bearing pathological forms related to latency or resistance to the development of advanced clinical stages [ 70 ]. These authors observed a significant increase of the level of these proteins in infected animals, especially with lesions characterized by a low bacterial load and with predominance of a cell-mediated immune response.…”
Section: Discussionmentioning
confidence: 99%
“…The differential proteomic analysis combined with immunohistochemical validation highlighted several changes occurring in PTB tissues and provided novel molecular information on the distinct levels of tissue involvement that can be found within the asymptomatic, paucibacillary condition. Other studies have investigated the levels of inflammatory acute-phase proteins (haptoglobin and serum amyloid A) developed during the course of MAP infection in serum as potential serum markers for the identification of sub-clinically infected cows bearing pathological forms related to latency or resistance to the development of advanced clinical stages [ 70 ]. These authors observed a significant increase of the level of these proteins in infected animals, especially with lesions characterized by a low bacterial load and with predominance of a cell-mediated immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Esta patología lleva a una infección que desencadena un proceso inflamatorio crónico granulomatoso a nivel intestinal en rumiantes domésticos y salvajes (Mallikarjunappa et al, 2020;McAloon et al, 2019). Aunque es común en dichos rumiantes, tiene elevada prevalencia en los hatos lecheros, lo cual genera graves consecuencias económicas y efectos adversos sobre el bienestar animal (Espinosa et al, 2020;Ozsvari et al, 2020;Sanchez et al, 2020).…”
Section: Artículos Originalesunclassified
“…A number of studies have previously identified potential biomarkers in MAP-infected animals (16,19,20). Acute phase proteins such as haptoglobin and serum amyloid A were significantly increased in various stages of paratuberculosis infection with different types of lesions (20). Shaughnessy et al identified three fecal biomarkers (hsa-miR-658, hsa-miR-92a-3p, and hsa-miR-501-5p) that were significantly upregulated in fecal samples of cattle with JD (19).…”
Section: Introductionmentioning
confidence: 99%
“…Biomarkers are measurable indicators that represent physiological alterations during disease progression. A number of studies have previously identified potential biomarkers in MAP-infected animals ( 16 , 19 , 20 ). Acute phase proteins such as haptoglobin and serum amyloid A were significantly increased in various stages of paratuberculosis infection with different types of lesions ( 20 ).…”
Section: Introductionmentioning
confidence: 99%